2007
DOI: 10.1007/s00122-006-0480-2
|View full text |Cite
|
Sign up to set email alerts
|

A 1,000-loci transcript map of the barley genome: new anchoring points for integrative grass genomics

Abstract: An integrated barley transcript map (consensus map) comprising 1,032 expressed sequence tag (EST)-based markers (total 1,055 loci: 607 RFLP, 190 SSR, and 258 SNP), and 200 anchor markers from previously published data, has been generated by mapping in three doubled haploid (DH) populations. Between 107 and 179 EST-based markers were allocated to the seven individual barley linkage groups. The map covers 1118.3 cM with individual linkage groups ranging from 130 cM (chromosome 4H) to 199 cM (chromosome 3H), yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
192
2
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(211 citation statements)
references
References 67 publications
10
192
2
1
Order By: Relevance
“…We also expected that there could be a somewhat higher rate of exon SNPs in EST sequences from wild-type and cultivated barley than in those from only cultivated barley because of mutations associated with domestication. However, our SNP rate was not as high as expected compared with the rates of 17-45% reported for three mapping populations by Stein et al (2007). This difference may be due to the higher detection rate of intron SNPs by Stein et al (2007) and the higher expected similarity in coding sequences between these accessions of wild-type and cultivated barley.…”
Section: Snp Typing 17% Caps 9%contrasting
confidence: 92%
See 1 more Smart Citation
“…We also expected that there could be a somewhat higher rate of exon SNPs in EST sequences from wild-type and cultivated barley than in those from only cultivated barley because of mutations associated with domestication. However, our SNP rate was not as high as expected compared with the rates of 17-45% reported for three mapping populations by Stein et al (2007). This difference may be due to the higher detection rate of intron SNPs by Stein et al (2007) and the higher expected similarity in coding sequences between these accessions of wild-type and cultivated barley.…”
Section: Snp Typing 17% Caps 9%contrasting
confidence: 92%
“…Mapped ESTs also provide access to other genomes, particularly that of rice (Oryza sativa L.), based on sequence similarity. Stein et al (2007) found significant micro-collinearity between the rice and barley genomes using a consensus barley map with 1032 EST-based loci assayed using a combination of marker assays (including 607 RFLPs). Comparative genomic analysis of barley ESTs and rice genome sequences will enable detection of undiscovered barley genome sequences.…”
Section: Introductionmentioning
confidence: 98%
“…In barley, molecular mapping for different traits has been an area of active research, which led to the identification of many markers for several important traits (Steffenson et al, 1996;Tuberosa and Salvi, 2004;Bilgic et al, 2005;Stein et al, 2007). In this study we found that with a large population and precise phenotypic characterization it is possible to detect molecular markers for a trait such as spot blotch resistance that is under polygenic control, even though some loci display large effects.…”
Section: Ssr Analysismentioning
confidence: 87%
“…The HvCslF3 gene could not be mapped directly, but it must also be at this position, given that it is on the same barley BAC as HvCslF4. Barley and rice genes tentatively identified as orthologs were generally located in syntenous regions of the rice and barley genomes (Stein et al, 2007), although chromosomal translocations coupled with local breakdown of colinearity made it difficult to make unequivocal conclusions in some cases (data not shown).…”
Section: Mapping the Barley Hvcslf Genesmentioning
confidence: 99%